2015
DOI: 10.7554/elife.05502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic BMP signaling polarized by Toll patterns the dorsoventral axis in a hemimetabolous insect

Abstract: Toll-dependent patterning of the dorsoventral axis in Drosophila represents one of the best understood gene regulatory networks. However, its evolutionary origin has remained elusive. Outside the insects Toll is not known for a patterning function, but rather for a role in pathogen defense. Here, we show that in the milkweed bug Oncopeltus fasciatus, whose lineage split from Drosophila's more than 350 million years ago, Toll is only required to polarize a dynamic BMP signaling network. A theoretical model reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 71 publications
10
64
0
Order By: Relevance
“…In the jewel wasp Nasonia vitripennis, representing the Hymenoptera (the outgroup to all other holometabolous insects), BMP patterns the entire axis, whereas Toll is only required locally to induce mesoderm formation (Özüak et al, 2014). In the milkweed bug Oncopeltus fasciatus (a hemimetabolous insect), Toll lacks all instructive roles for tissue specification; it only polarizes BMP signalling, which in turn patterns the DV axis (Sachs et al, 2015). Taken together, the DV gene regulatory network (GRN) of Tribolium deviates from that of Drosophila in many interesting ways, but has not diverged as much as the DV-GRN of more basally branching insects, making it a preferable choice for direct molecular comparisons with Drosophila.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the jewel wasp Nasonia vitripennis, representing the Hymenoptera (the outgroup to all other holometabolous insects), BMP patterns the entire axis, whereas Toll is only required locally to induce mesoderm formation (Özüak et al, 2014). In the milkweed bug Oncopeltus fasciatus (a hemimetabolous insect), Toll lacks all instructive roles for tissue specification; it only polarizes BMP signalling, which in turn patterns the DV axis (Sachs et al, 2015). Taken together, the DV gene regulatory network (GRN) of Tribolium deviates from that of Drosophila in many interesting ways, but has not diverged as much as the DV-GRN of more basally branching insects, making it a preferable choice for direct molecular comparisons with Drosophila.…”
Section: Introductionmentioning
confidence: 99%
“…Although the immune function of Toll is conserved from flies to vertebrates, a DV patterning function of Toll has not been observed outside the insects. Indeed, analysis of DV patterning in more basally branching insects indicates that during insect evolution Toll signalling progressively gained the complex morphogen function found in modern flies (Lynch and Roth, 2011;Özüak et al, 2014;Sachs et al, 2015). The red flour beetle Tribolium castaneum provides an interesting intermediate position within this evolutionary series.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, knockdown of Rp‐Toll2 displaces the position of the embryonic rudiment along the egg AP axis, in addition to alterations along the DV axis of the embryo (Berni et al ., ). In Oncopeltus it was shown that Of‐Toll knockdown also changes the position of DV gene expression territories along the AP axis (Sachs et al ., ). Therefore, it is possible that the AP and DV axes in Hemiptera are not independently established as in the model Diptera Drosophila melanogaster , but are rather integrated by common elements as also suggested for Apis mellifera (Wilson et al, ).…”
Section: Embryonic Developmentmentioning
confidence: 97%
“…A recent study in the Hemiptera Oncopeltus suggests that the Toll pathway only serves as a spatial cue to polarize BMP signals by enhancing the BMP inhibitor sog at the ventral side (Sachs et al ., ). Similarly to vertebrate and spider early patterning (reviewed in (Bier and De Robertis, ), Oncopeltus BMP is required for sog repression along the DV axis (Sachs et al ., ). In Rhodnius , Rp‐Toll knockdown results in loss of ventral mesoderm and mesodermal gene expression, as well as zygotic sog expression (Berni et al ., ).…”
Section: Embryonic Developmentmentioning
confidence: 97%
“…Notably, the A‐P and D‐V axes in Drosophila are distinct and are determined through different pathways (Hartenstein and Chipman, ). There is evidence to suggest that this distinction is not so clear in other insects (Berni et al, ; da Fonseca et al, ; Sachs et al, ; Wilson and Dearden, ).…”
Section: Introductionmentioning
confidence: 99%